Molten salt shielded pyrolysis of biomass waste: Development of hierarchical biochar, salt recovery, CO2 adsorption. (15th February 2023) - Zhu, Xiefei; Sun, Mingzhe; Zhu, Xinzhe; Guo, Wenwen; Luo, Zejun; Cai, Wenfei; Zhu, Xifeng
Graphical abstract: Highlights: Porous hierarchical biochar was novelly fabricated from biomass waste. Eutectic molten salt was used as a medium for carbonization-activation. Mechanism of molten salt-assisted preparation of biochar was revealed. Recovery and migration of molten salts were investigated. Biochar assisted by molten salt in air had better CO2 adsorption performance. Abstract: To investigate the facile conversion of biomass wastes into carbon-based adsorbents with efficient carbon capture, porous hierarchical biochar was novelly fabricated by molten salt-assisted pyrolysis under different inducing atmospheres (air and nitrogen) and temperatures. The pyrolysis characteristics of biomass waste in molten salt (K2 CO3 -Na2 CO3 -Li2 CO3 ) were probed by a thermogravimetric analyzer-differential scanning calorimeter (TG-DSC). Further, the physicochemical properties of biochar, recovery of molten salt, and CO2 adsorption performance were investigated comprehensively. The molten salt biochar had a high specific surface area (324.21–788.81 m 2 g −1 ). The biochar prepared in the air had a better CO2 adsorption capacity of up to 72.42 mg g −1, which was 20 % higher than the CO2 adsorption capacity of the biochar prepared in a nitrogen atmosphere. In addition, the recovery of molten salt was higher in the air-induced atmosphere. At an induction temperature of 900 °C, the recovery ratio of potassium in the air atmosphere was twice as high as that in nitrogen. Meanwhile, the potassium and sodium contents embedded in the biochar were lower in the air atmosphere. The pathway presented here will provide a novel and simple approach for the large-scale preparation of carbon-based adsorbents from biomass waste.